Evaluation of environmental management and its correlation with eco-efficiency in public institutions in Peru - Floriano Rodríguez, Ronald (2024)
The study aims to determine the relationship between environmental management and eco-efficiency of workers in public institutions in Peru. For this, a quantitative approach with a correlational design was proposed, in which 320 employees from various public institutions participated. Data collection was carried out through two Likert-type questionnaires, and the Spearman's Rho coefficient was used to obtain the correlation levels. The results showed a positive correlation (0.768) between environmental management and eco-efficiency, indicating that better implementation of environmental management practices is associated with more efficient use of resources within institutions. In conclusion, the importance of promoting policies and training on environmental management in the public sector is highlighted, as this not only contributes to environmental preservation but also has a direct impact on the operational efficiency of entities.